2002
DOI: 10.1038/sj.bjc.6600413
|View full text |Cite
|
Sign up to set email alerts
|

Potential role of levocarnitine supplementation for the treatment of chemotherapy-induced fatigue in non-anaemic cancer patients

Abstract: Ifosfamide and cisplatin cause urinary loss of carnitine, which is a fundamental molecule for energy production in mammalian cells. We investigated whether restoration of the carnitine pool might improve chemotherapy-induced fatigue in non-anaemic cancer patients. Consecutive patients with low plasma carnitine levels who experienced fatigue during chemotherapy were considered eligible for study entry. Patients were excluded if they had anaemia or other conditions thought to be causing asthenia. Fatigue was ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
55
1
2

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 94 publications
(61 citation statements)
references
References 21 publications
(40 reference statements)
3
55
1
2
Order By: Relevance
“…After 1 week of supplementation, 13 of 15 subjects increased total and free carnitine along with decreases in fatigue, as measured by Brief Fatigue Inventory scale, and Karnofsky performance status. Similar responses were seen in a group of patients receiving cisplatin or isofosfamide chemotherapy [185]. After 1 week of 4 g of carnitine daily, 45 of 50 subjects with abnormal fatigue significantly improved (P < .001) and they maintained their gains through the next cycle of chemotherapy.…”
Section: Fatiguesupporting
confidence: 63%
See 1 more Smart Citation
“…After 1 week of supplementation, 13 of 15 subjects increased total and free carnitine along with decreases in fatigue, as measured by Brief Fatigue Inventory scale, and Karnofsky performance status. Similar responses were seen in a group of patients receiving cisplatin or isofosfamide chemotherapy [185]. After 1 week of 4 g of carnitine daily, 45 of 50 subjects with abnormal fatigue significantly improved (P < .001) and they maintained their gains through the next cycle of chemotherapy.…”
Section: Fatiguesupporting
confidence: 63%
“…Decreased dermatitis [162] Chamomile Decreases fatigue [184][185][186][187] Black cohosh extracts in breast cancer patients with menopausal symptoms Decreases vasomotor symptoms in some trials [189,191] Green or black tea in leukoplakia Improved abnormality [194,195] Green tea extract in high-grade intraepithelial neoplasia of the prostate without conventional therapy Decreased progression to frank prostate cancer [196] Pomegranate juice in prostate cancer patients with rising PSA after radiation or surgery…”
Section: Grifola Umbellatae In Bladder Cancermentioning
confidence: 99%
“…We identified three studies (9% of total) of l-carnitine in the treatment of CRF [49][50][51]. These were all open-label prospective designs with 12-50 participants.…”
Section: L-carnitinementioning
confidence: 99%
“…Disrupted carnitine metabolism may result in chemotherapy-related fatigue. Previous clinical trials have examined the effects of carnitine supplementation in resolving carnitine deficiencies and its association with fatigue in this population [14,[18][19][20][21][22][23]. The majority of these trials have found carnitine supplementation to significantly improve both carnitine status and measures of fatigue with minimal adverse effects.…”
Section: Discussionmentioning
confidence: 99%